2013
DOI: 10.1186/1472-6882-13-348
|View full text |Cite
|
Sign up to set email alerts
|

Norartocarpetin from a folk medicine Artocarpus communis plays a melanogenesis inhibitor without cytotoxicity in B16F10 cell and skin irritation in mice

Abstract: BackgroundMany natural products used in preventive medicine have also been developed as cosmeceutical ingredients in skin care products, such as Scutellaria baicalensis and Gardenia jasminoides. Norartocarpetin is one of the antioxidant and antityrosinase activity compound in Artocarpus communis; however, the cytotoxicity, skin irritation and antimelanogenesis mechanisms of norartocarpetin have not been investigated yet.MethodsIn the present study, cell viability in vitro and skin irritation in vivo are used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…On the other hand, activated p38 MAPK and Erk1/2 signaling stimulate microphthalmia‐associated transcription factor expression and tyrosinase transcription to lead to melanin synthesis, implying that the activation of p38 MAPK or Erk1/2 signaling may result in melanin accumulation by activation of tyrosinase. Therefore, p38MAPK and Erk1/2 activation can be involved in both positive and negative actions in anti‐melanogensis . In the present study, we showed that all CBMEOs inhibited melanogenesis in B16BL6 cell and elevated α ‐MSH‐decreased phosphorylation of p38 MAPK and Erk1/2.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…On the other hand, activated p38 MAPK and Erk1/2 signaling stimulate microphthalmia‐associated transcription factor expression and tyrosinase transcription to lead to melanin synthesis, implying that the activation of p38 MAPK or Erk1/2 signaling may result in melanin accumulation by activation of tyrosinase. Therefore, p38MAPK and Erk1/2 activation can be involved in both positive and negative actions in anti‐melanogensis . In the present study, we showed that all CBMEOs inhibited melanogenesis in B16BL6 cell and elevated α ‐MSH‐decreased phosphorylation of p38 MAPK and Erk1/2.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, p38MAPK and Erk1/2 activation can be involved in both positive and negative actions in anti-melanogensis. [10][13] [14] In the present study, we showed that all CBMEOs inhibited melanogenesis in B16BL6 cell and elevated a-MSHdecreased phosphorylation of p38 MAPK and Erk1/2. Although there are conflicting reports about the role of p38 MAPK and Erk1/2 activation in melanogenesis, our results indicate that CBMEOs may inhibit B16BL6 cell melanogenesis at various levels through activation of both p38 MAPK and Erk1/2 signaling pathway.…”
Section: 3mentioning
confidence: 76%
See 2 more Smart Citations
“…Modulation of p38 phosphorylation prevented excessive melanin synthesis through the accelerated degradation of melanogenic enzymes . Norartocarpetin (C 15 H 10 O 6 ), a flavone, which can be found in plants such as A communis , Artocarpus heterophyllus, and Artocarpus dadah was proposed to downregulate MITF expression via JNK‐ and p38‐dependent pathway . ERK and JNK phosphorylation causes MITF ubiquitination and degradation, whereby downregulating melanin biosynthesis .…”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%